Practice of core competence training for orthopedic nurses in Hunan Province of China - Yang Zhou; Yabin Guo; Liya Huang; Biyun Zeng (BMC Nursing)
Abstract Objectives This study aims to present a preliminary exploration of an orthopedic nurse specialist training program in Hunan Province, China, and to explore the effectiveness of training. Methods The training programme consisted of one month of theoretical training and two months of clinical practice training. The training content was set around four modules: theoretical knowledge, professional skills, comprehensive practice, and professional development. The application effect of the curriculum was examined via a nonrandomized controlled experimental study. From December 2022 to December 2023, a total of 102 orthopedic specialist nurses from the selected training bases were trained, and we evaluated the effectiveness of the training by using the reaction, learning, behavioral, and results layers of Kirkpatrick Training Evaluation model. Before and after the training, the core competencies of the training participants were evaluated via the Core Competencies Questionnaire for Orthopedic Nurse Specialists, and paired t tests were used to compare the core competencies before and after the training. Results In total, 102 trainees in Hunan Province participated in the training program. The final score of the training trainees was 89.01 ± 2.16. All trainees passed theoretical and clinical practice examinations and trainee evaluations. Their core competencies significantly improved after training (P < 0.001). The overall satisfaction rate of the trainees with the theoretical and practical courses was 100%. Conclusion The orthopedic nurse specialist training program demonstrated science and effectiveness and improved the core competencies of nurses in providing orthopedic specialist care. The curriculum system is comprehensive and reliable and can be used as a reference for training orthopedic specialty nurses.